Remodeling of the Posterior Cerebral Artery P1-Segment after Pipeline Flow Diverter Treatment of Posterior Communicating Artery Aneurysms - Miguel S. Litao; Jan-Karl Burkhardt; Omar Tanweer; Eytan Raz; Paul Huang; Tibor Becske; Maksim Shapiro; Howard Riina; Peter K. Nelson (MDPI AG, 2021)
Introduction: Flow diverters such as the pipeline embolization device (PED) cause hemodynamic changes of the treated vessel segment. In posterior communicating artery (PcomA), aneurysms' unique anatomic consideration have to be taken in account due to the connection between the anterior and posterior circulation. We hypothesize that in conjunction with PcomA remodeling, there will also be remodeling of the ipsilateral P1 segment of the posterior cerebral artery (PCA) after PED treatment for PcomA aneurysms. Methods: We retrospectively collected radiological as well as clinical data of PcomA aneurysm patients treated with PED including PcomA and P1 vessel diameters before and after treatment as well as patient and aneurysm characteristics. Results: Overall, 14 PcomA aneurysm patients were included for analysis and PED treatment was performed without complications in all patients. In 10 out of 14 patients (71%), a decrease in PcomA diameter was observed and there was a significant mean decrease of 0.78 mm in PcomA diameter on angiographic last follow-up (LFU) (p = 0.003). In the same patient population (10 out of 14 patients), there was meanwhile a significant mean increase of 0.43 mm in the ipsilateral P1 segment diameter observed (p = 0.015). These vessel remodeling effects were in direct correlation with aneurysm occlusion since all of these patients showed aneurysm occlusion at LFU while 29% showed only partial occlusion without vessel remodeling effects. A decrease in PcomA diameter was directly associated with aneurysm occlusion (p = 0.042). There were no neurologic complications on LFU. Conclusion: In the treatment of PcomA aneurysms with PED, the P1 segment of the PCA increases in diameter while the PcomA diameter decreases. Our results suggest that this remodeling effect is associated with aneurysm occlusion and decrease of PcomA is hemodynamically compensated for by an increase in the ipsilateral P1 diameter.